Healthy lifestyle as a necessary condition for self-realization of a modern student in higher educational institutions - Sokolovskaya, I. A.; Zarytska, V. V.; Grishina, T. A.; Kovtun, R. A.; Bulanov, V. A.; Frolova, G. S.; Соколовська, Ірина Анатоліївна (Запорізький державний медичний університет, 2021)
The educational process in higher education involves not only education and upbringing, but also the recovery of the student. No one disputes the fact that today the amount of education exceeds all permissible norms of perception and is characterized by the impossibility of full assimilation by the student of the amount of knowledge, which is constantly growing.